THE Utilization of Family Medicine Plant in Nias Islands, North Sumatra Province - Adam Smith Bago (Publisher Cv. Inara, 2020)
Based on preliminary observations, it was found that the people in Nias Islands,North Sumatra province had used medicinal plants for a long time and had inheritedthem from generation to generation. So that many people still use medicinal plants.This study aims to determine the types of family medicinal plants used by thecommunity, how to mix or process family medicinal plants, and public perceptionsof family medicinal plants. This research is a type of qualitative research withdescriptive methods with 125 respondents. Collecting data by observation,interviews, documentation. The data analysis technique uses three stages, namelydata reduction, data presentation, and drawing conclusions or verification. Fromthe research results, there were 23 plant species used by the community in NiasIsland as Family Medicinal Plants. The method of concocting family medicinalplants varies greatly, depending on the type of plant and disease, the people ofSambulu village have good perceptions about family medicinal plants. Suggestionsare expected to maintain the habit of using medicinal plants, and also teach them tochildren or young people.